CLINICAL AND NEUROLOGICAL ASPECTS OF THYROID FUNCTION DISTURBANCE IN THE ELDERLY - Shomurodova D.S; Dzhurabekova A.T (Journal Park Publishing, 2022)
The study of the clinical features of neurological insufficiency in the elderly against the background of thyroid dysfunction seems to be an urgent problem. Based on the analysis of the examined patients over 60 years of age with thyroid dysfunction, a relationship was found between a decrease in the production of thyroid hormones and clinical and neurological disorders. It turned out that the lack of thyroid hormones in the elderly changes the clinical picture of the disease, accompanying more pronounced shifts in cognitive impairment, vestibulo-ataxic disorders, worse prognosis in terms of neuropathies, up to the syndrome of myopathy.
Keywords: old age; thyroid hormones; cognitive impairment